Systematic Review: Position Changes After Transfemoral Percutaneous Coronary Intervention - Indriani Merlyn Manueke; Yanny Trisyani; Nurlaeci Nurlaeci (Padjadjaran Acute Care Nursing Journal, 2019)
Background. Percutaneous Coronary Intervention (PCI) is the gold standard diagnostic test for Coronary Heart Disease (CHD). To minimize complications after PCI, patient activity is limited to bedrest for 2-24 hours. But the long bedrest can cause complaints of back pain and discomfort. This systematic review aims to identify the position changes in the first 6 hours after PCI for back pain and discomfort. Metode. Three electronic databases were used to carry out systematic searches namely Pubmed, CINAHL ebsco and ProQuest. The keyword combination is 'percutaneous coronary intervention' AND 'position change' OR 'changing position' OR 'early mobilization' NOT 'Literature Review' OR 'review of the literature' OR 'overview' OR 'Systematic Review' OR 'meta analysis’. The inclusion criteria used were articles with the last 12 years of research 2007 - 2019, quantitative research, English and Indonesian, peer review, randomized controlled trial and quasi experiment. The article search results found 49 articles on CINAHL ebsco, 81 articles on PubMed and 273 articles on ProQuest. A total of 13 articles met the inclusion criteria and were analyzed. Results. From 13 articles, 6 articles reported a decrease in complaints of back pain and discomfort after changing positions in the first 6 hours in bed. 4 articles indicate the same thing after a change of position made the first 6 hours then walking beside the bed. And 3 articles reported a decrease in complaints of back pain and discomfort after ambulation in the first 6 hours. Conclusion. Changes in position within a period of 6 hours after PCI can reduce the incidence of back pain and discomfort that is felt by patients.Keywords: position changes, percutaneous coronary intervention